SAT-009 SSRI Use in the Peripartum Period Regulates Mammary Gland Parathyroid Hormone Related Protein (PTHrP) by a Serotonylation-Dependent Mechanism - Sheftel, Celeste (J Endocr Soc, 2020)
During lactation, a woman experiences a considerable amount of bone loss and recent studies suggest bone deficits persist years postpartum. Furthermore, selective serotonin uptake inhibitors (SSRIs), which are often prescribed to women experiencing peripartum depression, have been linked to osteopenia. Serotonin signaling can increase parathyroid hormone related protein (PTHrP), a bone remodeling protein which liberates calcium for the milk. Additionally, fluoxetine (a common SSRI) results in increased mammary gland serotonin content and PTHrP, and treatment during the peripartal period reduced maternal bone mineral density. One proposed mechanism of serotonin action is by its covalent addition to proteins by transglutaminase (TG2), termed serotonylation. We therefore investigated whether the combination of fluoxetine and lactation can exacerbate maternal bone loss and the underlying mechanism. We hypothesized that SSRI-induced serotonin signaling in the lactating mammary gland increases PTHrP through a serotonylation-dependent mechanism. Treatment of mouse mammary epithelial cells (HC11) with fluoxetine significantly upregulates PTHrP gene expression and the concentration of its downstream effector, cAMP, over control (P < 0.0004). Furthermore, treatment of the HC11 cells with fluoxetine in addition to a TG2 inhibitor, monodansylcadaverine, restores PTHrP mRNA expression to levels observed in the control. Small g-proteins have emerged as a common target protein for serotonylation. Currently, our data suggest that the g-proteins, RhoA and Rab4, are potential serotonylation targets in the mammary gland. Together these data suggest that the molecular process of serotonyation in HC11 cells links serotonin signaling to increased PTHrP expression. Future work is directed at using the cre-lox system to genetically ablate serotonylation using a WAP(Cre)/TG2(Flox) transgenic mouse to determine whether decreasing serotonylation in vivo in the mammary gland during lactation improves maternal bone mass.